Tunable Plasmonic Band-Pass Filter with Dual Side-Coupled Circular Ring Resonators - Liu, Dongdong (Sensors (Basel), 2017)
A wavelength band-pass filter with asymmetric dual circular ring resonators in a metal-insulator-metal (MIM) structure is proposed and numerically simulated. For the interaction of the local discrete state and the continuous spectrum caused by the side-coupled resonators and the baffle, respectively, the transmission spectrum exhibits a sharp and asymmetric profile. By adjusting the radius and material imbedded in one ring cavity, the off-to-on plasmon-induced absorption (PIA) optical response can be tunable achieved. In addition, the structure can be easily extended to other similar compact structures to realize the filtering task. Our structures have important potential applications for filters and sensors at visible and near-infrared regions.